African Neotermes: redescriptions of imago and soldier castes of N. aburiensis and N. agilis (Isoptera, Kalotermitidae) - Ebenezer O. Onagbola; Rudolf H. Scheffrahn (ZooKeys, 2017)
We redescribe the winged imagos and soldiers of two equatorial African species, Neotermes aburiensis Sjöstedt and N. agilis (Sjöstedt) and describe their unique character attributes. The imago of N. aburiensis is adorned with unique spatulate-pointed setae. The soldier of N. aburiensis is unique among Neotermes in possessing a phragmotic forehead. The imago of N. agilis is small and unique among Neotermes in having complete coalescence of radial sector and median veins in the forewing while the soldier of N. agilis has a broad pronotum.